‘Happeners…don’t merely dig the scene, they make it’: The Social Meaning of the Work of Art in Allan Kaprow’s Happenings - Routledge, Laura (Nordic Journal of English Studies, 2020)
This paper looks at Allan Kaprow’s Happenings through the framework of Peter Bürger’s 1971 Theory of the Avant-Garde. It suggests that Kaprow’s Happenings project can be read as a detailed investigation into the way in which the category ‘art’ was formulated in his society, and an exploration of alternative possibilities for the social meaning and function of works of art excluded by this dominant ontology. The paper focuses specifically on Kaprow’s interrogation of the dominant understanding of the relationship between the art work and the spectator in the mid-century American art world, and the alternatives to this model that his Happenings proposed. Throughout the course of the 1960s, I demonstrate, Kaprow painstakingly explored and developed these alternatives, slowly formulating a model for the social function and meaning of the category ‘art’ that decentred hegemonic ideas about artistic autonomy and sought to ‘reintegrate art into the praxis of life’ (Bürger, 22).